Revision of Cirratulus (Cirratulidae: Polychaeta) from Argentina, with the description of three new species and a key to identify all species of the area - Saracho-Bottero, M. Andrea (2019)
Introduction: The taxonomy of Cirratulidae is not easy due to the diagnostic characters currently accepted change through ontogeny, in some cases, there are even difficulties to separate juveniles from adults. Among the Cirratulus species cited, described and considered as valid for Argentina are Cirratulus jucundus (Kinberg, 1866), Cirratulus patagonicus (Kinberg, 1866) and Cirratulus mianzanii Saracho Bottero, Elías & Magalhães, 2017. Objetive: This study made a revision of Cirratulus includes material deposited in the Museo de Ciencias Naturales de La Plata (MLP) and specimens collected privately by J.M. Orensanz that was donated to the laboratory of Bioindicadores Bentónicos of the National University of Mar del Plata. Methods: The specimens were examined with optical equipment (microscope and stereomicroscope) and also by a scanning electron microscope (SEM). Results: A complete examination of the material, revealed a higher number of species than those already mentioned. In the present work, three new species are described from the intertidal and subtidal areas of the Argentine continental shelf: Cirratulus orensanzii n. sp.; Cirratulus knipovichana n. sp. and Cirratulus alfonsinae n. sp. Conclusions: The knowledge about the taxonomy of the family as well as the updating of the geographic registries contributes to the biodiversity of the region, which is of great importance to carry out both ecological studies and conservation plans.